2023
DOI: 10.3390/ijerph20042926
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Carcinoma Burden and Its Attributable Risk Factors in China: Estimates and Forecasts from 1990 to 2050

Abstract: Nasopharyngeal carcinoma (NPC) is an uncommon and aggressive malignant head and neck cancer, which is highly prevalent in southern and southwestern provinces in China. The aim of this study was to examine the disease burden and risk factors of nasopharyngeal carcinoma in China from 1990 to 2019 and to predict the incidence trends from 2020 to 2049. All data were extracted from the 2019 Global Burden of Disease (GBD) study. Joinpoint regression and age-period-cohort (APC) models were chosen to analyze prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Similarly, more males drink alcohol than females in China. The Scientific Research Report on Dietary Guidelines for Chinese Residents (2021) showed that the drinking rate was 64.5% in males and 23.1% in females, while the smoking rate for males was 50.5% and that for females was 11.8% 34 . Besides smoking and alcohol use, sex hormones are also one of the risk factors of larynx cancer 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, more males drink alcohol than females in China. The Scientific Research Report on Dietary Guidelines for Chinese Residents (2021) showed that the drinking rate was 64.5% in males and 23.1% in females, while the smoking rate for males was 50.5% and that for females was 11.8% 34 . Besides smoking and alcohol use, sex hormones are also one of the risk factors of larynx cancer 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The Scientific Research Report on Dietary Guidelines for Chinese Residents (2021) showed that the drinking rate was 64.5% in males and 23.1% in females, while the smoking rate for males was 50.5% and that for females was 11.8%. 34 Besides smoking and alcohol use, sex hormones are also one of the risk factors of larynx cancer. 35 Compared with normal controls, patients with larynx cancer have higher testosterone levels, but their estrogen levels are at the same levels, indicating that testosterone may promote the development of larynx cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A Jointpoint regression model was constructed using the method of previous study [ 19 ], in which a log-linear regression model was used to estimate the average annual percent change (AAPC) and its 95% confidence interval (CI) reflecting the trend of ASMR and ASDR from 1990 to 2019. In addition, we used Pearson correlation analysis to further understand the association between SDI and the burden of NCDs associated with occupational asbestos exposure at the national and regional levels.…”
Section: Methodsmentioning
confidence: 99%
“…The model establishes a segmented regression based on the temporal characteristics of the disease distribution, splits the study time into different intervals through a number of connecting points, and optimizes the trend fitting for each interval. The regression coefficients for each interval were weighted to obtain the average annual percentage change (AAPC) and its 95% confidence interval (95% CI) to estimate the overall change over the study period ( 17 , 18 ), as follows:…”
Section: Methodsmentioning
confidence: 99%